High-Throughput, Parallel Flow Cytometry Screening of Hundreds of Cell Surface Antigens Using Fluorescent Barcoding - Drápela, Stanislav; Fedr, Radek; Vacek, Ondřej; Remšík, Ján; Souček, Karel (Methods in molecular biology (Clifton, N.J.), 2022)
Multicolor flow cytometry allows for analysis of tens of cellular parameters in millions of cells at a single-cell resolution within minutes. The lack of technologies that would facilitate feasible and relatively cheap profiling of such a number of cells with an antibody-based approach led us to the development of a high-throughput cytometry-based platform for surface profiling. We coupled the fluorescent cell barcoding with preexisting, commercially available screening tools to analyze cell surface fingerprint at a large scale. This powerful approach will help to identify novel biomarkers and druggable targets and facilitate the discovery of new concepts in immunology, oncology, and developmental biology.
Keywords: Research; antigeny povrchové; výzkum; Cell surface phenotyping; Fluorescent cell barcoding; Fluorescent Dyes; High-throughput screening; Antigens, Surface; Flow Cytometry; biologické markery; průtoková cytometrie; Biomarkers; fluorescenční barviva; Multicolor flow cytometry